2014
DOI: 10.3168/jds.2013-7369
|View full text |Cite
|
Sign up to set email alerts
|

Effects of folic acid and vitamin B12 supplementation on culling rate, diseases, and reproduction in commercial dairy herds

Abstract: This study was undertaken to determine the effect of a combined folic acid and vitamin B12 supplement given in early lactation on culling rate, metabolic disorders and other diseases, and reproduction in commercial dairy herds. A total of 805 cows (271 primiparous and 534 multiparous cows) in 15 commercial dairy herds were involved. Every 2mo from February to December 2010 and within each herd, cows were assigned according to parity, previous 305-d milk production, and calving interval to 5mL of either (1) sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
2
18
0
1
Order By: Relevance
“…On the other hand, folic acid is part of coenzymes that participate in the transfer of one-carbon unit in several biochemical pathways. Milk production during the first 200 d of lactation was increased linearly in multiparous, but not in primiparous cows fed a diet that provided 0, 2, or 4 mg of folate/kg of body weight [ 25 ], and an intramuscular administration of folic acid (320 mg/week) and vitamin B 12 (10 mg/week) about 1 month before and 2 months after calving reduced time to first breeding [ 26 ]. Gagnon et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, folic acid is part of coenzymes that participate in the transfer of one-carbon unit in several biochemical pathways. Milk production during the first 200 d of lactation was increased linearly in multiparous, but not in primiparous cows fed a diet that provided 0, 2, or 4 mg of folate/kg of body weight [ 25 ], and an intramuscular administration of folic acid (320 mg/week) and vitamin B 12 (10 mg/week) about 1 month before and 2 months after calving reduced time to first breeding [ 26 ]. Gagnon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Providing supplemental folic acid and vitamin B 12 by weekly injections increased milk production by 12% (Preynat et al, 2009a,b). However, in a field study of 805 cows in 15 herds (Duplessis et al, 2014a), weekly injections of folate and vitamin B 12 through the transition period generally did not affect health outcomes or milk yield, although milk protein percentage was increased (Duplessis et al, 2014b).…”
Section: Introductionmentioning
confidence: 91%
“…However, in the recent past, numerous studies have shown an increase in milk production or component yield (or both) when cows are supplemented with vitamin B compounds (Sacadura et al, 2008;Chen et al, 2011;Evans and Mair, 2013). Similarly, a positive effect of supplementation on health has also been reported, especially in early lactation dairy cows (Graulet et al, 2007;Duplessis et al, 2014;Li et al, 2016), which is achieved via improvement in metabolic efficacy. Based on results reported by Santschi et al (2005), Schwab et al (2006), and Sacadura et al (2008), a deficit for folic acid, pantothenic acid, and pyridoxine was estimated in cows, which indicates that the requirements for B vitamins could have changed in modern dairy cows.…”
Section: Introductionmentioning
confidence: 99%